Surface modification of the alloy Ti-7.5Mo by anodization for biomedical applications - Escada, Ana Lucia do Amaral [UNESP]; Muñoz Chaves, Javier Andres [UNESP]; Rosifini Alves Claro, Ana Paula [UNESP] (Trans Tech Publications, 2016)
The purpose of this study was to evaluate the TiO2 nanotubes growth and the variation in its diameter to improve the surface properties of Ti-7.5Mo to use for biomedical applications. For the nanotubes TiO2 growth, the samples were anodized in glycerol and ammonium fluoride and divided according to the anodizing potential at 5V to 10V and 24 hour time. The surfaces were examined by scanning electron microscope (SEM), X-ray analysis (XRD) and contact angle measurements. The average tube diameter, ranging in size from 13 to 23 nm, was found to increase with increasing anodizing voltage. It was also observed a decrease in contact angle in accordance with the increase in the anodizing potential. The X-ray analysis showed the presence of anatase phase in samples whose potential was 10V and this condition represents a simple surface treatment for Ti- 7.5Mo alloy that has high potential for biomedical applications.
Keywords: Anodization; Nanotubes; Self-organization; TiO2 nanotubes